Optimizing Poster Media for Speaking Micro Skills at Gontor Islamic Teacher Training Students - Aries Fachriza; Alya Fitroh Andriyani; Eka Indah Nuraini; Dinar Dipta; Dian Nashrul Munif (English Education Department, Faculty of Teacher Training and Education, Islamic University of Jember, 2025)
The mastery of speaking micro-skills, particularly grammatical accuracy, is essential for students in Islamic boarding schools to achieve effective communication. However, traditional approaches often lack interactive learning support. This study evaluates the effectiveness of poster media in improving students’ speaking proficiency through the Monday Talk Program at ITTC Darussalam Gontor. A quasi-experimental non-equivalent control group design was implemented, with participants selected through purposive sampling based on similar proficiency levels and the availability of intact classes. The experimental group received poster-based instruction, while the control group used mind mapping. Pre-test and post-test scores were collected to measure learning gains. The results show a significant improvement (p = 0.000) in the experimental group, indicating that poster media effectively enhance grammatical accuracy in speaking. These findings suggest that integrating visual media into structured speaking programs supports more engaging and effective learning. In conclusion, poster media represent a valuable instructional tool for strengthening students’ grammatical proficiency in Islamic boarding school contexts.